A study on building condition audit at public building case study: Majlis Perbandaran Subang Jaya / Jackry Julai - Julai, Jackry (Faculty Architecture, Planninng and Surveying, 2015)
The purpose of this research is to study the existing process and procedure of building condition audit for public building in Malaysia conducted by Majlis Perbandaran Subang Jaya (MPSJ) specifically for food court building. In order to carry out this study, first, exploratory study should be done in order to determine the problem statement and current issues regarding the building condition audit especially public building in our country. Journal, textbook, newspapers and internet sources were the main sources that will be used to carry out the exploratory study before proceed with the problems statement and objectives of the research. After the exploratory had been carried out, the aim and objectives of the study will be listed after the title of the research had been chosen. Based on the objectives, methodology in order to achieve the objectives will be prepared including the methods that will be used to carry out the study. In this study, there are three methods were chosen including interview with local authority; site observation and questionnaire with distribute and collect at the same time technique. Next steps will involves data analysis and discuss the finding based on the method approach. This will help to determine whether the method used can help to achieve the objectives of the research. Then data analysis will be made based on the questionnaire that had been distribute during carry out the observation on case study. Comparison will be made based on interviews and literature reviews with data and direct observation made in case study. Any weakness will be identified based on the comparison and suggestion will be made to the authority in order t improve their practice towards a better practices in future. In this research the objectives one were to determined the current practices of building condition audit being conduct in MPSJ and this objectives had been achieves by make an appointment with the officer and asked the question regarding the process and procedure they used when it involves with the building audit. Besides that, this method also being used in order to get information regarding common maintenance problems being faced especially for public building especially food court building. This method can help to achieve the second’s objectives of this research. Apart from that, direct observation also another approach being used in order to determine the actual problems that occurred on the site. This will help to make comparison between observation and information gained from the interview with the local authority officer. For third objectives, questionnaire method was used i order to know the satisfaction level of the building user regarding the performance of the building in term of it condition, cleanliness and the process and procedure of condition audit conduct by the authority. From data analysis based on the questionnaire distribution, most of the user not satisfied with certain of the elements, services and process and procedures conduct by the authority. Based on this analysis, suggestion and recommendation can be made in order to improve the current practice that had been conduct by the authority for a better plan in the future. Further research should be conduct in order to ensure the current practices being conduct have some improvement in the future based on the previous report. Building condition audit was not only a process of inspection that being used to check the condition and performances of the building but it also can help to lower the cost for maintenance work. A better plan and schedule should be made in order to ensure the value of the building will be maintained and the performances of the building satisfied the user.